COGNITIVE BEHAVIOR THERAPY UNTUK MENINGKATKAN SELF-ESTEEM PADA ANAK USIA SEKOLAH - Islamiah, Nur; Daengsari, Dini P.; Hartiani, Fenny (Jurnal Ilmu Keluarga dan Konsumen, 2015)
In this research, Cognitive Behavior Therapy (CBT) was used to increase low self-esteem on a school-age children (boy, 10 years old). Cognitive Behavior Therapy (CBT) is a treatment that aimed to reduce psychological distress and maladaptive behavior by altering cognitive processes. The design of this study was single-subject research design specifically experimental study which used one participant to verify the effectiveness of a theraphy. This treatment consists of 13 sessions, with 2 sessions for the assessment (pre-test and post-test), 10 session for the treatment sessions, and 1 session for the evaluation). The duration of each session approximately 1,5 - 2 hours. Based on observations, interviews, pre-test and post-test, CBT was effective to increase selfesteem on the participant.